Finding a Mentor and Being a Mentor - László Bruszt (Sociologica)
Becoming a professional social scientist, getting inside, finding your way in a complex field, and improving your position requires lots of diverse skills and helpful ties that one cannot get at most universities. In this short piece I first describe how I could find a mentor for myself in communist Hungary, and how he, and later also a second mentor, have helped me to position myself in a transnational scholarly field. I also discuss how I have used the lessons I have learnt from them in my role as supervisor to over thirty doctoral dissertations.